TINGKAT KEMISKINAN DI WILAYAH KOTA MEDAN SERTA SOLUSI PEMERINTAH DALAM MENANGANINYA - Hanifah Ramadhani; Nur Afria Nanda Safitri; Wanhar Nasution; Juliana Nasution (Transformasi: Journal of Economics and Business Management, 2022)
This study intends to find out the level of poverty in the Medan city area and how the government's efforts/solutions deal with it. The research method used is a qualitative approach which is a literature study. This study also uses secondary data, namely the results of the percentage of the population below the poverty line from the Central Statistics Agency (BPS). Seen in 2017 the number of people below the poverty line in the city of Medan amounted to 204 thousand people, which is a fairly high number, In 2018, the number of poor people fell by 18,000, and in 2019 alone the number of people below the poverty line fell in the city of Medan around 183 thousand people but in 2020 the poverty rate in the city of Medan is still around 183,000 people, but in 2021 the poverty rate in the city of Medan will increase dramatically to around 193,000 people